Composite of calcium cobaltite with praseodymium-doped ceria: A promising new oxygen electrode for solid oxide cells. (10th August 2021) - Araújo, Allan J.M.; Loureiro, Francisco J.A.; Holz, Laura I.V.; Grilo, João P.F.; Macedo, Daniel A.; Paskocimas, Carlos A.; Fagg, Duncan P.
Abstract: Calcium cobaltites have emerged as an attractive alternative to be used in Solid Oxide Cells (SOCs), due to their excellent thermal compatibility with standard electrolytes that may privilege these compounds among state-of-the-art SOC electrodes. Nonetheless, their electrochemical performances have been strongly limited by poor oxygen ion transport. Hence, we report a new composite electrode containing the misfit calcium cobaltite [Ca2 CoO3-δ ]0.62 [CoO2 ] (C349) phase combined with Ce0.8 Pr0.2 O2-δ (CPO). A comparative study is presented between this composite and the standard La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF), in terms of their microstructures, number of depositions, and resultant electrochemical properties. Such tailoring permits the best C349/CPO composite electrode to attain high levels of electrochemical performance that rival with the standard LSCF material. This successful result is highly relevant, as it can provide insight into the most critical optimisation factors for similar SOC electrodes that intrinsically suffer from similarly low levels of ionic transport. Highlights: Novel C349/CPO composite as oxygen electrode for solid oxide cells. Effect of film thickness on the polarisation resistance of C349 electrodes. C349 electrodes suffer from intrinsic low ionic conductivity compared to LSCF.